2014
DOI: 10.3390/nu6062360
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of 24-Hour Urinary Sodium Excretion Using Spot Urine Samples

Abstract: The present study evaluated the reliability of equations using spot urine (SU) samples in the estimation of 24-hour urine sodium excretion (24-HUNa). Equations estimating 24-HUNa from SU samples were derived from first-morning SU of 101 participants (52.4 ± 11.1 years, range 24–70 years). Equations developed by us and other investigators were validated with SU samples from a separate group of participants (n = 224, 51.0 ± 10.9 years, range 24–70 years). Linear, quadratic, and cubic equations were derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
61
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 23 publications
(62 reference statements)
14
61
1
5
Order By: Relevance
“…With the Kawasaki formula, the same accuracy will only be reached for individuals with intake ranging from 12 to 18 g/day. This conclusion is in agreement with recent reviews [21][22][23][24] , but different from other studies that considered the estimations of salt consumption based on casual urine to be adequate for epidemiological analyses or for follow-up of individual consumption 8,9,11,12,32,33 . The acceptance of methods, however, was based on analyses of agreement.…”
supporting
confidence: 75%
“…With the Kawasaki formula, the same accuracy will only be reached for individuals with intake ranging from 12 to 18 g/day. This conclusion is in agreement with recent reviews [21][22][23][24] , but different from other studies that considered the estimations of salt consumption based on casual urine to be adequate for epidemiological analyses or for follow-up of individual consumption 8,9,11,12,32,33 . The acceptance of methods, however, was based on analyses of agreement.…”
supporting
confidence: 75%
“…The assessment revealed contradictory conclusions. Kawasaki's equation seems to overestimate sodium excretion by differing degree [49][50][51]. Whereas Cogswell et al [49] found an average overestimation of more than Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Presented are median and interquartile range (box) and the 5th and 95th percentile (whiskers) Table 5 Correlation of creatinine estimates obtained with various equations Kawasaki [33] Tanaka [32] Toft [31] Johner [36] Kawasaki [ [50] concluded that the estimates with Kawasaki's equation were the least biased. Brown's equation, in contrast, seems to underestimate daily sodium excretion by a differing degree [49][50][51]. Cogswell et al [49] concluded that results obtained with Brown's equation are least biased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(12,13), con los datos presentados no podemos indicar cuánto es la ingesta, cuál es la fuente de sodio ingerida ni cuanto es el consumo diario de sodio. El valor que presenta la excreción de sodio en una muestra espontánea de orina a nivel individual no tiene ningún significado y no está recomendado por ninguna guía clínica.…”
Section: Rango Intercuartilounclassified